2012
DOI: 10.1089/hum.2011.125
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunity to AAV-6, 8, and 9 in Normal and Dystrophic Dogs

Abstract: Adeno-associated virus (AAV)-6, 8, and 9 are promising gene-delivery vectors for testing novel Duchenne muscular dystrophy gene therapy in the canine model. Humoral immunity greatly influences in vivo AAV transduction. However, neutralizing antibodies to AAV-6, 8, and 9 have not been systemically examined in normal and dystrophic dogs. To gain information on the seroprevalence of antibodies to AAV-6, 8, and 9, we measured neutralizing antibody titers using an in vitro transduction inhibition assay. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…In these two animals we found high levels of NAb not only to AAV8 but also to AAV1, AAVrh10, AAV5, and AAV9. Although the data obtained in this study were generated using animals from a single colony, they support previous findings in humans worldwide, 4,12 where subjects positive for one AAV serotype were also found positive for other AAV serotypes.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In these two animals we found high levels of NAb not only to AAV8 but also to AAV1, AAVrh10, AAV5, and AAV9. Although the data obtained in this study were generated using animals from a single colony, they support previous findings in humans worldwide, 4,12 where subjects positive for one AAV serotype were also found positive for other AAV serotypes.…”
Section: Resultssupporting
confidence: 87%
“…Many species, including dogs, sheep, pigs, macaques, and humans, have serum-circulating neutralizing antibodies (NAbs) to AAV at various levels, [4][5][6][7][8][9][10][11] with a strong correlation between AAV NAbs and the AAV serotype recovered from tissues. For example, the most prevalent AAV serotype in humans, AAV2, is also associated with a higher prevalence of AAV2 NAbs in the population, 10,12,13 whereas, on the contrary, AAV8, a nonhuman AAV, has higher prevalence among rhesus and cynomolgus macaques.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent findings suggest that AAV-6 is not ideal for systemic gene delivery in dogs. First, investigators including us have shown that there exists a strikingly high prevalence of AAV-6 neutralization antibody in dog blood (Rapti et al, 2012;Shin et al, 2012b). As a matter of fact, we have detected AAV-6 neutralization antibody ( ‡1:40) in the serum sample of every newborn puppy we examined (a total of 30 puppies; Shin et al, 2012b).…”
Section: Discussionmentioning
confidence: 87%
“…123 This is in sharp contrast to what has been shown with direct AAV-6 injection in dog muscle. 101,102,124 We believe that the difference is likely because of (1) the high-level preexisting AAV-6 neutralization antibody in the canine circulation, 36,125 or (2) the presence of galectin 3 binding protein (G3BP) in dog serum. 126 It has been shown that G3BP can cause AAV-6 particle aggregation and compromise transduction.…”
Section: Dystrophin-independent Gene Therapy In the Cdmd Modelmentioning
confidence: 99%
“…To overcome this shortcoming, we have generated hybrid DMD dogs. [35][36][37][38][39][40] These dogs carry the genetic information from several breeds and thus can better reflect the human condition.…”
mentioning
confidence: 99%